MENELISIK PERAN TENAGA AHLI ANGGOTA LEGISLATIF - Permana, Yogi Setya; Adaba, Pandu Yuhsina (Jurnal Penelitian Politik, 2011)
Performance oftheparliament would be maximal ifit s been back up with optimal support system Part ofthesupport systems is parliamentary expert staff As a matter offact performance and role ofthe expert staffs as partofsupporting Indonesia s parliamentary is not in optimal condition The condition is due to absence ofclear anddetail regulation on the role anffunction ofparliament expert staff As a result ofthat condition many distortionsin role andfunction ofexpert staffhas been dailyfact in the parliament This paper is to analyze thatproblem andgive some recommendation related to the problem